Surgical therapy of cutaneous squamous cell carcinoma: our experience - Simonacci, Francesco; Bertozzi, Nicolò; Grieco, Michele Pio; Grignaffini, Eugenio; Raposio, Edoardo (Acta Biomedica Atenei Parmensis, 2018)
Introduction: Cutaneous squamous cell carcinoma (cSCC) is the second most common skin cancer, with an excellent prognosis after surgical removal. However, nodal metastasis are present in about 5% of cases and the death rate is about 2%. Presentation of case: The aim of this study is to report our experience about the surgical treatment of cSCC at the Cutaneous, Regenerative, Mininvasive and Plastic Surgery Unit, University of Parma, Italy, between January 2014 and February 2016. We statistically analyzed the group of patients regarding the average age, gender, localization and size of the lesions. The surgical margins of the excisions are studied and we report the results obtained after a follow up of 3 to 25 months. Discussion: Between January 2014 and February 2016 in our Cutaneous, Regenerative, Mininvasive and Plastic Surgery Unit, we removed 36 squamous cell carcinomas, including 11 cSCCs in situ. The average annual incidence of squamous cell carcinoma in northeast of Italy is about 28,9  cases per 100,000 individuals.The number of cSCCs that we removed is lower than the Italian average. In our opinion, this is due to an increase in the early diagnosis of precancerous lesions and their medical or surgical treatment. This reduces the incidence of squamous cell carcinomas developing from precancerous lesions. Conclusion: The excision of cutaneous squamous cell carcinoma should be undertaken with a safety margin of at least 0.9 mm to minimize recurrence and metastasis.